Assessment of Job Satisfaction Level and Its Associated Factors among Health Workers in Addis Ababa Health Centers: A Cross-Sectional Study. (30th September 2020) - Aklilu, Mesfin; Warku, Waleleng; Tadele, Wogayehu; Mulugeta, Yimer; Usman, Hussene; Alemu, Amelework; Abdela, Sintayehu; Hailemariam, Alemnesh; Birhanu, Endalkachew
Abstract : Health workers account for the largest share of public expenditures on health and play an important role in improving the quality of health services. There is concern that poor health worker performance limits the effectiveness of health systems strengthening efforts. A cross-sectional study was conducted from September to October 2016 in Addis Ababa health centers. Data were collected from 420 healthcare workers using a pretested and structured questionnaire by trained data collectors. EPI Info 7 was used for data entry, and analysis was done by SPSS version 20. Bivariate and multivariate logistic analyses were used to identify factors associated with the outcome variable and to control confounders. P values less than 0.05 were considered statistically significant. The overall job satisfaction level accounts for 53.8% with 95% CI of (48.9%, 59.0%). Marital status and professional qualification were the potent predictors of job satisfaction. Respondents who never married were 1.65 times more likely to be satisfied in their job than those married or divorced (AOR: 1.65 (95% CI: 1.02, 2.66)). Laboratory professionals and nursing professionals were 2.74 and 1.97 times more likely to be satisfied in their job compared to health officers (AOR: 2.47 (95% CI: 1.14, 6.59) and AOR: 1.97 (95% CI: 1.12, 3.48), respectively). More than half of the healthcare workers in the study area were satisfied in their job. Marital status and healthcare workers' profession type were predictors of job satisfaction. Research studies indicate that there is a positive relationship between performance and job satisfaction. Accordingly, the present study aimed at determining the level of job satisfaction of health workers and its associated factors in the health centers of Addis Ababa, Ethiopia.